2015
DOI: 10.1073/pnas.1502461112
|View full text |Cite
|
Sign up to set email alerts
|

Myosin VI regulates gene pairing and transcriptional pause release in T cells

Abstract: Naive CD4 T cells differentiate into several effector lineages, which generate a stronger and more rapid response to previously encountered immunological challenges. Although effector function is a key feature of adaptive immunity, the molecular basis of this process is poorly understood. Here, we investigated the spatiotemporal regulation of cytokine gene expression in resting and restimulated effector T helper 1 (Th1) cells. We found that the Lymphotoxin (LT)/TNF alleles, which encode TNF-α, were closely jux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 54 publications
4
28
0
Order By: Relevance
“…This approach could enable enhanced RNAPII binding to initiate transcription and facilitate rapid recycling of RNAPII to drive higher expression levels. Such a mechanism would also fit with the observation that myosin VI functions in gene pairing (Zorca et al, 2015). We have previously shown that myosin VI interacts with RNAPII through actin (Fili et al, 2017), present within the RNAPII complex.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This approach could enable enhanced RNAPII binding to initiate transcription and facilitate rapid recycling of RNAPII to drive higher expression levels. Such a mechanism would also fit with the observation that myosin VI functions in gene pairing (Zorca et al, 2015). We have previously shown that myosin VI interacts with RNAPII through actin (Fili et al, 2017), present within the RNAPII complex.…”
Section: Discussionsupporting
confidence: 68%
“…The minus-end directed myosin, Myosin VI ( Figure 1A), has been shown to bind DNA through its cargo binding domain (CBD) and couple itself to RNAPII in an actin-dependent manner through the motor domain (Fili et al, 2017). It has been revealed that the ability of myosin VI to bind DNA and its ATPase activity are both critical for transcription in vitro (Cook et al, 2018, Fili et al, 2017, and myosin VI can function in gene pairing (Zorca et al, 2015). Recently, myosin VI has been shown to actively undergo directed motion in the nucleus in response to transcription stimulation (Große-Berkenbusch et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study suggests that the need for heterotypic chains may be derived from poor binding to mammalian proteasome of ubiquitin chains that are linked exclusively by K11 (Grice et al, 2015). Notably, a few reports suggest a nuclear function for myosin VI (Vreugde et al, 2006; Zorca et al, 2015). In this subcellular compartment, myosin VI may interact with proteins modified by K11-linked chains to regulate transcription and viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…The first study showed that RNA constitutes a significant fraction of chromatin date back over 50 years ago [41,42]. Later studies provide evidence to support the idea that a nuclear matrix is made of insoluble proteins and RNA in an interphase nucleus [43]. Treatment of RNase A leads to clumping of chromatin onto nuclear lamina and nucleolus [44,45], indicating an indispensable role of RNA in the nuclear architecture.…”
Section: Chromatin Associated Rnasmentioning
confidence: 98%